1991
DOI: 10.1055/s-2007-1025440
|View full text |Cite
|
Sign up to set email alerts
|

Testikuläre Funktion nach OPA / COMP-Chemotherapie ohne Procarbazin bei Jungen mit Morbus Hodgkin

Abstract: Gonadal function was evaluated in 25 boys treated for Hodgkin's disease according to the DAL-HD-85 protocol with OPA- or OPA/COMP-chemotherapy (vincristine-prednisone-adriamycine/cyclophosphamide-vincristine-m ethotrexate- prednisone). All boys were in first continuous complete remission for 6 to 45 months at chronological ages varying from 14.0 to 18.9 years. Testosterone, basal and GnRH-stimulated LH- and FSH-levels were measured. Gonadal function was normal in 16 patients treated with 2 cycles of OPA-chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Among the eligible studies, the reported percentage of patients with elevated FSH ranged from 0% to 100% (median 51.5%). Nine studies used the generally accepted cutoff value of 10 IU/L to determine high FSH serum level, indicating damage to spermatogenesis ( Sherins et al , 1978 ; Hassel et al , 1991 ; Heikens et al , 1996 ; Mackie et al , 1996 ; Müller et al ., 1996 ; van den Berg et al , 2004 ; Servitzoglou et al ., 2015 ; Brignardello et al , 2016 ; Felicetti et al , 2020 ). The other studies used higher cutoff values (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Among the eligible studies, the reported percentage of patients with elevated FSH ranged from 0% to 100% (median 51.5%). Nine studies used the generally accepted cutoff value of 10 IU/L to determine high FSH serum level, indicating damage to spermatogenesis ( Sherins et al , 1978 ; Hassel et al , 1991 ; Heikens et al , 1996 ; Mackie et al , 1996 ; Müller et al ., 1996 ; van den Berg et al , 2004 ; Servitzoglou et al ., 2015 ; Brignardello et al , 2016 ; Felicetti et al , 2020 ). The other studies used higher cutoff values (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Patients in TG2 or TG3 received no procarbazine, but mean cyclophosphamide doses ranging from 2 004 mg/m 2 (TG2) to 3 722 mg/m 2 (TG3). No major testicular damage was noted in TG2 and TG3 demonstrating, that cyclophosphamide in mean cumulative doses < 3 800 mg/m 2 had no toxic effect on testicular function [25].…”
mentioning
confidence: 77%
“…61 As such, updated chemotherapy regimens dropped procarbazine or included dacarbazine, a chemically similar compound with less side effects. [62][63][64] In prepubertal boys, procarbazine was shown to contribute the most to the gonadotoxic effect of the MOPP regimen, as assessed through hormonal measurements. Indeed, both FSH and LH levels were shown to remain elevated at a median follow-up time of 52 months after treatment.…”
Section: Carboplatinmentioning
confidence: 99%
“…Although the standard MOPP (nitrogen mustard, vincristine, procarbazine, and prednisone) regimen revealed high efficacy, the high rates of permanent infertility following treatment soon led clinicians to develop alternative regimens 61 . As such, updated chemotherapy regimens dropped procarbazine or included dacarbazine, a chemically similar compound with less side effects 62–64 …”
Section: Clinical Evidence Of Infertility: Harmful Effects Of Chemoth...mentioning
confidence: 99%